2012
DOI: 10.3109/0142159x.2012.714881
|View full text |Cite
|
Sign up to set email alerts
|

Empathy in Iranian medical students: Measurement model of the Jefferson Scale of Empathy

Abstract: Background: Empathy is an important factor in patient-physician relationship that has beneficial effects in medical practice. Jefferson Scale of Empathy (JSE) has been specifically designed to assess empathy in health professionals (HP-version) and related students (S-version). Few validation studies have been performed on S-version of the scale. Aims: To examine empathy in a large sample of Iranian medical students, and also to study factor structure and psychometric properties of the Persian translation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
101
1
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(124 citation statements)
references
References 23 publications
16
101
1
6
Order By: Relevance
“…This was in disagreement with what was reported about American and Iranian medical students who having increase level of empathy in basics year comparing to the clinical years. They explained this by the fact that these students were put through a course to implementing ethics and communication skills training in the curriculum in the basic years aiming to improving the doctor-patient relationship in clinical practice [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…This was in disagreement with what was reported about American and Iranian medical students who having increase level of empathy in basics year comparing to the clinical years. They explained this by the fact that these students were put through a course to implementing ethics and communication skills training in the curriculum in the basic years aiming to improving the doctor-patient relationship in clinical practice [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated 22 that there is gender variability in relation to empathy in a study in 18 dental schools in Latin America. As a consequence, it is not possible to state categorically that women are more empathetic than men in all populations studied, despite the fact that authors have observed the opposite [8,[23][24][25][26][27].…”
Section: General Empathymentioning
confidence: 74%
“…Also, most of the researchers agree that on entering the clinical practice phase of training, and with increased contact with patients, empathy declines significantly (Neumann et al, 2011). Shariat and Habibi's (2013) study showed that the decline of empathy in medical education is not limited to medical schools in the Western world. The obtained lowest score should be related to not having a constructed communication skills training program during clerkships and internship in our school.…”
Section: Discussionmentioning
confidence: 99%
“…The gender difference in empathy has been attributed to intrinsic factors (e.g., evolutionary-biological gender characteristics) as well as extrinsic factors (e.g., interpersonal style in caring, socialization, and gender role expectation) (Hojat et al, 2002). Several studies have suggested that female medical students (Hojat et al, 2002;Chen et al, 2007;Hojat et al, 2009;Kataoka et al, 2009;Shariat and Habibi 2013;Wen et al, 2013) gain a higher score of empathy, possibly because they tend to value interpersonal relationships highly and have more competent understanding of emotions and caring attitude. On the other hand, few studies have shown no gender difference in empathy (Roh et al2010;Hamed et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation